The Influence of Perceived Usefulness, Perceived Ease of Use and Perceived Risk on Continuance Intention at E-Wallet DANA in Bandung - Mila Popi Purnama; Devilia Sari (Budapest International Research and Critics University, 2022)
Electronic wallets exist because of the fast-paced changes in people's lifestyles. However, some users are still worried about the big consequences, for example the reliability and security of the e-wallet. DANA is an e-wallet with >100 million users throughout Indonesia. With so many users, there is a need for an adequate security system. The operation of the technology should not require much effort. However, there are reviews that the DANA e-wallet still finds difficulties and there is a gap (gap) between perceived benefits, ease of use and perceived risk. The risk of using an e-wallet can affect the user experience and become a barrier to continued use. This study aims to see the existence of